Mixtures of Plant-Growth-Promoting Rhizobacteria Enhance Biological Control of Multiple Plant Diseases and Plant-Growth Promotion in the Presence of Pathogens - Liu, Ke; McInroy, John A; Hu, Chia-Hui; Kloepper, Joseph W (Plant disease, 2018)
Several studies have shown that mixtures of plant-growth-promoting rhizobacteria (PGPR) could enhance biological control activity for multiple plant diseases through the mechanisms of induced systemic resistance or antagonism. Prior experiments showed that four individual PGPR strains-AP69 (Bacillus altitudinis), AP197 (B. velezensis), AP199 (B. velezensis), and AP298 (B. velezensis)-had broad-spectrum biocontrol activity via antagonism in growth chambers against two foliar bacterial pathogens (Xanthomonas axonopodis pv. vesicatoria and Pseudomonas syringae pv. tomato) and one of two tested soilborne fungal pathogens (Rhizoctonia solani and Pythium ultimum). Based on these findings, the overall hypothesis of this study was that a mixture of two individual PGPR strains would exhibit better overall biocontrol and plant-growth promotion than the individual PGPR strains. Two separate greenhouse experiments were conducted. In each experiment, two individual PGPR strains and their mixtures were tested for biological control of three different diseases and for plant-growth promotion in the presence of the pathogens. The results demonstrated that the two individual PGPR strains and their mixtures exhibited both biological control of multiple plant diseases and plant-growth promotion. Overall, the levels of disease suppression and growth promotion were greater with mixtures than with individual PGPR strains.